Segmentation-Based Adaptive Support for Accurate Stereo Correspondence - Tombari, Federico; Mattoccia, Stefano; Di Stefano, Luigi (Advances in Image and Video Technology, 2007)
Significant achievements have been attained in the field of dense stereo correspondence by local algorithms based on an adaptive support. Given the problem of matching two correspondent pixels within a local stereo process, the basic idea is to consider as support for each pixel only those points which lay on the same disparity plane, rather than those belonging to a fixed support. This paper proposes a novel support aggregation strategy which includes information obtained from a segmentation process. Experimental results on the Middlebury dataset demonstrate that our approach is effective in improving the state of the art.